Best Answer

2x-3x+1 can be simplified (by combining like terms, or terms with the same number/type of variables) to -x+1. This is not an equation, but an "expression," meaning that there is no equals sign, and you cannot solve for x without an equals sign. If, for instance, that entire expression was equal to 7,

-x+1=7

-x = 6

x = -6

Q: How do you solve 2x-3x plus 1?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

1

sixteen m squared plus eight m plus 1

When simplified it is: 1-8x

2y + 7x + y-1?

That factors to (a + 1)(a + b) a = -1, -b b = -a

Related questions

1

-1 plus 1 = 0 plus 1 =1

sixteen m squared plus eight m plus 1

x+2x3x

1 + 1 = 2The process used to solve it is "addition."

you add the together and get 46

When simplified it is: 1-8x

2y + 7x + y-1?

2x3x-4= -24

a+a=1 2a=1 a=1/2

That factors to (a + 1)(a + b) a = -1, -b b = -a

This is an expression and you do not solve an expression, but you can factor this one.X2 + 3X4X2(1 + 3X2)========